2019
DOI: 10.3390/ma12121893
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Constitutive Models for 21-4N Heat Resistant Steel during High Temperature Deformation

Abstract: The Gleeble-1500D thermal simulation test machine was used to conduct the isothermal compression test on 21-4N at the strain rate ( ε ˙ ) of 0.01–10 s−1, the deformation temperature (T) of 1273–1453 K and the maximum deformation is 0.916. The data of the stress-strain (σ-ε) were obtained. Based on the σ-ε data, the Johnson-Cook (J-C), modified J-C, Arrhenius and Back-Propagation Artificial Neural Network (BP-ANN) models were established. The accuracy of four models were verified, analyzed and compared. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Table 2 shows coefficients of the polynomial for α, n, Q and lnA in the osA-type equation. After determining material parameters under different strains, the predicted stress can be determined based on Equation (17), which is shown in Figure 7.…”
Section: Establishing the Original Strain-compensated Arrhenius-type mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows coefficients of the polynomial for α, n, Q and lnA in the osA-type equation. After determining material parameters under different strains, the predicted stress can be determined based on Equation (17), which is shown in Figure 7.…”
Section: Establishing the Original Strain-compensated Arrhenius-type mentioning
confidence: 99%
“…To predict the hot flow stress of 10% Cr steel alloy, Abdallah et al [15] found the prediction accuracy of the strain-compensated Arrhenius-type model is higher than that of modified Johnson-Cook. Moreover, the previous comparative studies have found the strain-compensated Arrhenius-type equation can give a more accurate description of the relationship between flow stress and deformation conditions when compared with the modified Johnson-Cook, Johnson-Cook equations [16,17]. Moreover, based on the stress-strain data of T24 steel, a comparative study of Li et al [18] showed the predictability of the strain-compensated Arrhenius-type equation is stronger than that of the modified Zerilli-Armstrong equation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the parameter 1 H numerical simulation of impact of the obstacle at high-speed collision with the steel impactor was carried out using finite element package LS-DYNA [5]. LS-DYNA has a wide range of options for describing the behavior of elastoplastic materials under dynamic loads, but the choice of constants for a particular material is not an easy task, as it might seem at first glance [6][7][8].The problem was solved for 3D case in the Lagrangian formulation. Geometric model (see Fig.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Conducting experiments is the most direct and effective way to obtain the mechanical behavior of materials. Scholars have constructed material constitutive models [1][2][3] using experiments to describe the stress-strain response of materials, and then study the mechanical properties of materials. Xin, X.…”
Section: Introductionmentioning
confidence: 99%